Exogenous nitric oxide relieves iron-inhibitory effect on wheat seed germination - Shuqian Shi; Zhe Zhang; Rongrong Ma; Yihui Tao; Ziling Wang; Yingli Yang (Ecotoxicology and Environmental Safety)
Seed germination is critical for crop production and is sensitive to abiotic stresses. Considering that nitric oxide (NO) has been shown to ameliorate the negative effects of abiotic stress in several plants, we investigated the effect and mechanisms of exogenous NO in wheat seed germination under Fe stress, focusing on oxidative stress. Specifically, seeds of the wheat cultivar ‘Ningchun 4’ were treated with 1 mM FeCl3 (Fe) or with the NO donor sodium nitroprusside (SNP) and/or the specific NO scavenger 2-phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (PTIO). Changes in endogenous NO production, Fe content, starch mobilisation, and antioxidant enzyme activity were examined at the early (24 h) and late (72 h) germination stages. Notably, Fe and PTIO treatments reduced the germination potential, germination rate, germination index, and vitality index of wheat seeds during the early and late germination stages. Additionally, Fe and PTIO treatments reduced endogenous NO levels, increased starch, sucrose, and soluble sugar contents, induced oxidative stress, suppressed antioxidant enzymes, and downregulated nitrate reductase, NO synthase, and amylase activities. However, SNP treatment ameliorated Fe stress-induced inhibition of seed germination, increased NO levels, upregulated starch degradation, and improved the antioxidant system and reactive oxygen species scavenging. Conclusively, exogenous NO treatment alleviates the inhibitory effects of Fe on wheat seed germination by enhancing endogenous NO synthesis, promoting starch decomposition, and alleviating oxidative damage.